KINERJA KEUANGAN (KPRI) KARYA SEJAHTERA KECAMATAN KLABANG KABUPATEN BONDOWOSO JIKA DILIHAT RASIO KEUANGANNYA BERDASARKAN ANALISIS LAPORAN KEUANGAN PADA TAHUN 2013 SAMPAI TAHUN 2017 - Tri Astindari (STKIP PGRI SITUBONDO, 2017)
The goal to be achieved in this research is to find out how far the development of the financial performance (KPRI) of Karya Sejahtera, Klabang District, Bondowoso Regency when viewed from financial ratios for 5 years. The design of this research is field research. To determine which areas will be studied, the researcher uses purposive sampling method. The method of determining the research respondents is the population method and the sample method, the determination in choosing the method of determining the respondent will determine the success of the research. Data collection techniques in this study using observation, interviews, documentation. The data analysis technique is using Financial Ratio Analysis and Growth Ratio Analysis. From the results of the research conducted, it can be concluded that the state of economic profitability at KPRI